Deixis Analysis on The Song Lyric, Driver’s License by Olivia Rodrigo - Devana Agustina; Hendar Hendar (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The aim of this research is to find out the types of deixis used in the lyrics of the song, ‘Driver’s License’ which was realized in January 8, 2021 sung by Olivia Rodrigo. The song lyrics are associated with deixis as they express the song singer's or writer's feelings or emotions represented by some expressions of human thoughts, ideas and opinions. The main theory used to analyze the types of deixis consisting of person, place, time, social, and discourse is taken from Cruse (2000). This research conducted was using a descriptive qualitative research design since the data were obtained from the lyrics of the song. The results of the research showed that the number of the data on the types of deixis found in the lyric of the song were 77 data. It consisted of 57 data (74%) on person (personal) deixis, 11 data (14,3%) on time (temporal) deixis, 7 data (9,1%) on place (spatial) deixis, and 2 data (2,6%) on social deixis, and 0 data (0%)on discourse deixis.